Fractional-order position/force robot control - Ferreira, N. M. Fonseca (2019)
In this paper it is studied the implementation of fractional-order algorithms in position/force control of two cooperating robotic manipulaotrs. The performance and system robustness are analyzed in the time and frequency domains. The effect of backlash and flexibility at the robot joints is also investigated.